Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3846/1822-427x.2009.4.186-195
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Interlayer Shear Bond Devices for Asphalt Pavements

Abstract: For testing the bond between asphalt pavement layers quite a variety of methods were proposed and used during the last 30 years. In many publications some of these test methods and devices were described by presenting photographs and sketches. Often photographs show the functioning of the devices only insufficiently and detailed information regarding the test devices (e.g. gap width) and test conditions (e.g. loading function, normal force) are difficult to retrieve. The following paper summarises the test met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 8 publications
0
28
0
1
Order By: Relevance
“…Here, the effect of a given interlayer system may depend on the exact loading conditions (repeated thermal loading, traffic loading). Raab et al (2009), shear testing is recognized as a good and effective method for testing the interlayer bond of asphalt pavements. A first interlaboratory test was organized during the TC 206-ATB of the RILEM in order to compare the different shear test procedures to assess interlayer bonding properties in asphalt pavements (Piber et al 2009).…”
Section: Laboratory Testsmentioning
confidence: 99%
“…Here, the effect of a given interlayer system may depend on the exact loading conditions (repeated thermal loading, traffic loading). Raab et al (2009), shear testing is recognized as a good and effective method for testing the interlayer bond of asphalt pavements. A first interlaboratory test was organized during the TC 206-ATB of the RILEM in order to compare the different shear test procedures to assess interlayer bonding properties in asphalt pavements (Piber et al 2009).…”
Section: Laboratory Testsmentioning
confidence: 99%
“…Currently, tests available for pavement layer interface evaluation mainly focus on interface shear resistance. In addition, most existing tests are performed in monotonic mode, which is not representative of the pavement interface loading conditions under traffic [7]. Also, tests used to evaluate cracking resistance of interlayer materials require large specimens, which are relatively difficult to fabricate in the laboratory and more difficult to obtain from the field [8][9][10][11][12].…”
Section: Overviewmentioning
confidence: 99%
“…Different devices and testing procedures have been presented, divided in several types: Torque Test; Tensile Test (Pull-off Test); Pure Direct Shear Test and Direct Shear Test with Normal Stress Applied, but the lack of standards on these procedures allows the diffusion of ever new prototypes, typically used to better investigate the different factors affecting shear interface strength. The comparison between the proposed devices has shown that the shear test is a good and effective method for testing the interlayer bond of asphalt pavements (Raab et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Several factors concerning the surface, such as cleanness, dryness, roughness and age have been considered in the experimental plan to define the interaction between different surface characteristics of the underlying layer and the adhesion properties (Raab et al, 2009;Tashman et al, 2006). This result is also confirmed by Santagata et al (2008) that showed an increasing interlayer shear resistance for higher macro-texture.…”
Section: Introductionmentioning
confidence: 99%